Spike-timing-dependent plasticity induced in resting lower limb cortex persists during subsequent walking - Jayaram, Gowri; Santos, Lynette; Stinear, James W. (Brain research, 2007)
Transcranial magnetic stimulation (TMS) of human lower limb motor cortex paired with common peroneal nerve electrical stimulation produces a lasting modulation of motor cortex excitability following the principles of spike-timing-dependent plasticity. We previously demonstrated that this “paired associative stimulation” (PAS) protocol applied during walking induced a bidirectional modulation of cortical excitability. The present study tested the hypothesis that the excitability of lower limb motor cortex assessed during walking is increased when PAS is applied to the resting cortex. PAS was delivered as a block of 120 pairs at 0.5 Hz to healthy subjects ( n = 13) in three separate sessions. TMS intensity was related to the active threshold obtained in tibialis anterior (TA) during the late swing phase of walking. Therefore, intensities used were below resting thresholds. When PAS using TMS intensities above active threshold was applied to the resting cortex, the normalized amplitude of potentials evoked in TA during subsequent walking increased to 124%. Using the same parameters and applying PAS during the late swing phase of walking, response amplitude increased to 114% of baseline. When the TMS intensity was set to active threshold, PAS applied to the resting cortex did not significantly modulate cortical excitability.